Auditoría tributaria a la empresa sociedad civil M&S televisión, ubicada en la provincia de Pichincha cantón Quito sector la villa flora durante el período enero – diciembre del año 2012 - Mogollón Luje, Diana Carolina (2016)
The present research had as general objective analysis on tax obligations held by the company with the IRS (Internal Revenue Service), which consisted of the application of the tax audit of the company Civil Society M & S Television during the period 2012, We also use theoretical methods such as inductive method which allowed us to analyze the data, statements and registration that allowed us to reach a general conclusion and applying the deductive methodic one allowed us to expand, break down, knowing the reason why the activities and registrations made, as well as we applied research techniques like a survey that allowed out us to get real information from interviewers, it was applied to the junior accountant, 14 employees and 333 customers….